Organización de la cadena productiva del cuy en el valle del Mantaro proyectado al mercado nacional e internacional - Aliaga Balbín, Hélida (2016)
The general objective of the thesis is to establish the relationship between the organization and the competitiveness of the productive chain of guinea pigs in Mantaro Valley to projected to national and international market, and propose strategies to strengthen the organization and competitiveness of the chain. The focus of research is quantitative, the kind of research is applied, the range is correlational. The design used is non experimental traverse correlation. To research a special list of guinea pig producers who are organized in 19 associations based on the information provided by the Ministry of Agriculture in Junín and the SEPAR group was developed. Stratified sampling was used to determine the sample of 211 producers. The techniques used were the content analysis and the survey. The survey was structured in two parts, the first to evaluate the organization of the productive chain with 34 questions and the second to evaluate competitiveness, through the map of competitiveness of the appropriate IDB with 100 questions, in eight areas: production, marketing, quality, strategic planning, human talent, environmental management, information systems as well as accounting and finance From the statistical treatment of the data, a high level of perception of the variable organization of productive chains is obtained, as well as a level of average competitiveness. With the test of Spearman rank coefficient 0.590, it shows that there is a direct relationship between media and the organization and competitiveness of the productive chain of guinea pigs in the Mantaro Valley to be projected to the national and international market. The analysis is complemented by external indicators based on the competitive diamond approach of Michael Porter and a profile is proposed to make the guinea pig a flagship product to break down barriers and enter the international market.